Analisis Pengembangan Wakaf Uang melalui Koperasi Syariah pada Era 4.0 - Zahro, Dien Nur Aulia; Chaerunnisa, Ermina Septian; Hastuti, Fifi Maharyani (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2022)
Waqf in Indonesia is not optimal, mostly, because it only develops in non-productive sectors such as mosque, grave, and soon. The ministery of cooperatives andc SMEs (2020) recorded the number of sharia cooperatives throughout Indonesia as many as 4,046 units as of the end of December 2019. The number of cooperatives in Indonesia has positive impact on the the development of waqf. Thisarticle use qulitative reseach by using literature review. Based on this method, 21 literatures were obtained according to the theme has been decided. The results show that (1) the way to maximise the potential of waqf in development in the 4.0 era is by productive waqf through cash waqf. (2) the development of cash waqf through sharia cooperatives can be done by improving literacy, inclusion, and application of good corporate government.